OC-103 The impact of low fodmap dietary advice and probiotics on symptoms in irritable bowel syndrome: a randomised, placebo-controlled, 2 × 2 factorial trial. (22nd June 2015) - Staudacher, H; Lomer, MC; Lindsay, JO; Irving, PM; Whelan, K
Abstract : Introduction: Controlled trials using complete feeding diets have demonstrated that dietary restriction of fermentable carbohydrates (low FODMAP diet, LFD) reduces symptoms in patients with irritable bowel syndrome (IBS). However, a randomised, placebo controlled dietary advice trial has not been performed. Also, LFD has a negative impact on the gastrointestinal microbiota and the benefit of combining LFD with probiotics is unknown. This randomised controlled trial aimed to investigate the effect of LFD dietary advice with a probiotic on symptom response compared with a sham diet in patients with IBS. Method: Adults with IBS referred to a secondary care dietetic service were screened for inclusion (n = 162). Eligible patients were randomised to LFD or sham (placebo) dietary advice and to the multi-strain probiotic VSL#3 or placebo for 4 weeks in a 2 × 2 factorial design. The sham (placebo) diet was designed to be equivalent in nutrients and FODMAP content to habitual diet. Outcome measures included the global symptom question ('did you have adequate relief of your IBS symptoms over the last 7 days?') and the validated IBS symptom severity scale (IBS-SSS, maximum score 500) at baseline and follow up. Statistical analysis was performed using logistic and linear regression. Results: A total of 104 patients were recruited and 95 completed the study (63 females, 66%). There were 8 withdrawals (4 LFD, 4 sham) and 1 loss to follow up (sham). There was no significant interaction between diet (LFD/sham) and probiotic (VSL#3/placebo) for adequate relief or IBS-SSS. In the intention-to-treat analysis, a higher proportion of patients reported adequate relief at follow up in LFD (57%) versus sham (38%, p = 0.05; RR 1.51, 95% CI 0.99, 2.29) and for probiotic (57%) versus placebo (37%, p = 0.05, RR 1.52, 95% CI 0.99, 2.33). Mean IBS-SSS scores were significantly lower following the LFD versus sham (165.5 vs 231.8, p < 0.001) but not different for probiotic versus placebo (196.9 vs 201.7, p = 0.75), after adjusting for baseline values. Subscores for IBS-SSS were significantly lower after LFD versus sham for days of pain (28.6 vs 44.7, p < 0.001), distension (27.3 vs 41.6, p = 0.001) and satisfaction with bowel habit (40.7 vs 54.5, p < 0.001). Conclusion: This is the first randomised placebo-controlled trial evaluating the effect of LFD advice which demonstrates greater effectiveness compared with sham advice for IBS symptoms. The effectiveness of this probiotic is equivocal. Whether concomitant probiotic treatment is able to prevent the impact of LFD on the microbiota will be investigated. Disclosure of interest: None Declared.